1998
DOI: 10.1182/blood.v91.8.3044.3044_3044_3051
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Phospholipid Asymmetry in Human Thalassemia

Abstract: Phospholipid asymmetry in the red blood cell (RBC) lipid bilayer is well maintained during the life of the cell, with phosphatidylserine (PS) virtually exclusively located in the inner monolayer. Loss of phospholipid asymmetry, and consequently exposure of PS, is thought to play an important role in red cell pathology. The anemia in the human thalassemias is caused by a combination of ineffective erythropoiesis (intramedullary hemolysis) and a decreased survival of adult RBCs in the peripheral blood. This prem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
82
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(85 citation statements)
references
References 22 publications
3
82
0
Order By: Relevance
“…Several anemic conditions are paralleled by accelerated suicidal erythrocyte death, such as iron deficiency (13), phosphate depletion (14), hemolytic uremic syndrome (15), sepsis (16), malaria (17,18), Wilson's disease (19), sickle cell disease (20 -27), thalassemia (20,24,25,28,29), and glucose-phosphate dehydrogenase deficiency (25,30). Moreover, suicidal erythrocyte death is stimulated by a wide variety of endogenous mediators and xenobiotics (31)(32)(33)(34)(35)(36)(37).…”
mentioning
confidence: 99%
“…Several anemic conditions are paralleled by accelerated suicidal erythrocyte death, such as iron deficiency (13), phosphate depletion (14), hemolytic uremic syndrome (15), sepsis (16), malaria (17,18), Wilson's disease (19), sickle cell disease (20 -27), thalassemia (20,24,25,28,29), and glucose-phosphate dehydrogenase deficiency (25,30). Moreover, suicidal erythrocyte death is stimulated by a wide variety of endogenous mediators and xenobiotics (31)(32)(33)(34)(35)(36)(37).…”
mentioning
confidence: 99%
“…For example, the RBC membrane undergoes vesiculation under a variety of conditions, which include increased cytoplasmic calcium concentration, reduced ATP content and disruption of the membrane lipid-protein organization (Wagner et al, 1986)all of which are features characteristic of thalassaemic RBCs. It has been shown that vesicles and MPs from platelets and RBC strongly bind annexin V, a protein known for its interaction with negatively charged phospholipids such as phosphatidylserine (PS) (Shinar et al, 1987;Borenstain-Ben Yashar et al, 1993;Zwaal & Schroit, 1997;Kuypers et al, 1998). PS is one of the key membrane phospholipids that is normally located along the inner side of the membrane bilayer.…”
mentioning
confidence: 99%
“…PS is one of the key membrane phospholipids that is normally located along the inner side of the membrane bilayer. It is known to activate the alternative complement pathway and to support the formation of activated clotting enzymes when expressed on the outer lipid bilayer (Borenstain-Ben Yashar et al, 1993;Zwaal & Schroit, 1997;Kuypers et al, 1998;Freyssinet, 2003). An important insight into this procoagulant potential was corroborated by clinical studies showing elevated levels of circulating MPs in patients with an increased risk for thromboembolic events (i.e.…”
mentioning
confidence: 99%
“…In the congenital haemolytic anaemias, sickle cell disease and thalassaemia, an enhanced exposure of PS on the abnormal RBC surfaces has recently been found (Chiu et al, 1979(Chiu et al, , 1981Yashar et al, 1993;Kuypers et al, 1998). The addition of sickle or thalassaemic RBC with a PS-rich surface q 1999 Blackwell Science Ltd Correspondence: Dr Haruhiko Ninomiya, Division of Haematology, Institute of Clinical Medicine, University of Tsukuba, Tennodai 1-1-1, Tsukuba, Ibaraki 305-8575, Japan.…”
mentioning
confidence: 99%